2022
DOI: 10.3389/fddev.2022.855017
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Blood-Brain Barrier Resistance: Implications for Extracellular Vesicle-Mediated Drug Brain Delivery

Abstract: Drug delivery across the blood–brain barrier (BBB) has several challenges, especially toward targeting neurological diseases, due to tight and selective barrier function of the BBB. Several structural and functional components of this barrier contribute to restricting drug entry, such as interendothelial tight junctions (TJs), efflux transporters, drug-metabolizing enzymes, and crosstalk between the cells of the neurovascular unit. Among different strategies to overcome BBB resistance to therapeutic drug deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 119 publications
0
5
0
Order By: Relevance
“…The integrated defence systems of the BBB impose a major challenge for effective drug delivery and the treatment of many brain diseases. Over the past decade, multiple strategies to improve drug delivery across the BBB have focused on non-invasive techniques [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…The integrated defence systems of the BBB impose a major challenge for effective drug delivery and the treatment of many brain diseases. Over the past decade, multiple strategies to improve drug delivery across the BBB have focused on non-invasive techniques [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, EVs can be found in cerebrospinal fluid (CSF) and have been found to cross the BBB, emerging as novel biomarker sources to study neurodegenerative diseases [ 60 , 61 ]. For example, exosomes found in amyloid beta ( ) plaques, characteristic of Alzheimer’s disease, have been found to contain specific proteins, suggesting that they could serve as indicators of such [ 49 ].…”
Section: Exosomes As a Subset Of Extracellular Vesicles—their Origin ...mentioning
confidence: 99%
“…We demonstrated that exposure to HIV-1 increases EV release from human brain microvascular endothelial cells (HBMEC) and alter their Aβ cargo [ 20 ]. EVs having diverse origin, size, and cargo can be taken up by the target cells via several routes [ 21 ]. Importantly, HBMEC-derived EVs (HBMEC-EVs) carrying Aβ can be transferred to other cells of the neurovascular unit, including neural progenitor cells (NPCs), causing NPC dysfunction and their aberrant neurogenesis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%